Growth response of Great Basin limber pine populations to climate variability over the past 4002 years. (July 2021) - Millar, Constance I.; Delany, Diane L.; King, John C.; Westfall, Robert D.
Abstract: Tree-rings representing annual dates from live and deadwood Pinus flexilis at ten sites across the central Great Basin ( 38°N) yielded a cumulative record across 4002 years (1983 BC–AD 2019). Individual site chronologies ranged in length from 861–4002 years; all were continuous over their sample depths. Correlations of growth with climate were positive for water relations and mostly negative for summer temperatures. Growth was generally correlated across sites, with the central Nevada stands most distinct. Although growth was low during the Late Holocene Dry Period, variability marked this interval, suggesting that it was not pervasively dry. All sites had low growth during the first half of the Medieval Climate Anomaly, high growth during the mid-interval pluvial, and low growth subsequently. Little synchrony occurred across sites for the early Little Ice Age. After AD 1650, growth was depressed until the early twentieth century. Growth at all sites declined markedly ca. AD 1985, was similar to the lowest growth period of the full records, and indicative of recent severe droughts. A small rebound in growth occurred after ca. AD 2010. A strong signal for Atlantic Multidecadal Oscillation (AMO) occurred in growth response at most sites. The persistence of all stands despite climate variability indicates high resilience of this species.